Colistin Resistant mcr Genes Prevalence in Livestock Animals (Swine, Bovine, Poultry) from a Multinational Perspective. A Systematic Review - George Valiakos; Ioanna Kapna (Veterinary Sciences, 2021)
The objective of this review is to collect and present the results of relevant studies on an international level, on the subject of colistin resistance due to mcr genes prevalence in livestock animals. After a literature search, and using PRISMA guidelines principles, a total of 40 swine, 16 bovine and 31 poultry studies were collected concerning mcr-1 gene; five swine, three bovine and three poultry studies referred to mcr-2 gene; eight swine, one bovine, two poultry studies were about mcr-3 gene; six swine, one bovine and one poultry manuscript studied mcr-4 gene; five swine manuscripts studied mcr-5 gene; one swine manuscript was about mcr-6, mcr-7, mcr-8, mcr-9 genes and one poultry study about mcr-10 gene was found. Information about colistin resistance in bacteria derived from animals and animal product foods is still considered limited and that should be continually enhanced; most of the information about clinical isolates are relative to enteropathogens Escherichia coli and Salmonella spp. This review demonstrates the widespread dispersion of mcr genes to livestock animals, indicating the need to further increase measures to control this important threat for public health issue.